The location of culture - Bhabha, Homi K. (Routledge, 2004)
Rethinking questions of identity, social agency and national affiliation, Bhabha provides a working, if controversial, theory of cultural hybridity - one that goes far beyond previous attempts by others. In The Location of Culture, he uses concepts such as mimicry, interstice, hybridity, and liminality to argue that cultural production is always most productive where it is most ambivalent. Speaking in a voice that combines intellectual ease with the belief that theory itself can contribute to practical political change, Bhabha has become one of the leading post-colonial theorists of this era.